Investigation of Crash Impact Toward the Highway Impact Attenuator Structure Using Finite Element Analysis - Awgku Aji, Awgku Azrol Nur Afiq; Ismail, Al Emran (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study aims to investigate and evaluate the effectiveness of an impact attenuator designed for installation on roads. The goal is to identify the impact attenuator design that can best absorb kinetic energy from crash impacts. The study proposes the use of computational crash simulations to assess the safety performance of the impact attenuator, reducing the costs associated with development and testing of new safety designs. The analysis begins with studying the behavior of impact attenuator structures and accurately modeling them in numerical simulations using ANSYS Workbench. The simulations involve crashing the impact attenuator with a rigid object at various speeds to observe the resulting deformation and energy absorption. The review is divided into three categories: simulation tests of the existing model, simulation tests of an improved version of the previous model, and a comparison between the two simulation tests. The outcomes of these tests can then be examined and analyzed.